A stearic acidified-ZnO/methyl polysiloxane/PDMS superhydrophobic coating with good mechanical durability and physical repairability. Issue 11 (2nd November 2019) - Yu, Nanlin; Xiao, Xinyan; Pan, Guangming
Abstract: A robust stearic acidified-ZnO (SA-ZnO)/methyl polysiloxane/polydimethylsiloxane (PDMS) superhydrophobic coating had been fabricated on glass slide by a simple droplet-coating method. The obtained coating showed good superhydrophobicity with a water contact angle (WCA) above 150° and a water sliding angle (WSA) less than 2°. The surface morphology, roughness and components of the coating were analyzed by SEM, 3 D optical profiler and FT-IR, respectively. The SA-ZnO/methyl polysiloxane/PDMS superhydrophobic coating not only displayed good mechanical durability against sandpaper abrasion test and knife-scratch test, but also exhibited physical repairability to recover its superhydrophobicity after being exposed to some extreme conditions such as strong acid and alkali. This physical repair process could be repeated for many times until the coating was worn out. The coating also could maintain its superhydrophobicity under high-intensity UV irradiation and low/high temperature. The SA-ZnO/methyl polysiloxane/PDMS coating could be applied onto other substrates, including filter paper, cotton fabric and aluminium sheet. Graphical Abstract: UF0001